1991
DOI: 10.1148/radiology.179.3.2028000
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging evaluation of endometrial carcinoma: results of an NCI cooperative study.

Abstract: A prospective study to assess the usefulness of magnetic resonance (MR) imaging in the evaluation of endometrial carcinoma was undertaken by five institutions under the auspices of the National Cancer Institute. Six different MR imagers were used, ranging in magnetic field strength from 0.15 T to 1.5 T. For each unit, appropriate T1- and T2-weighted sequences in the transverse plane and T2-weighted sequences in the sagittal plane were used. Initially, 107 patients were entered in the study, but only 88 fulfill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
5

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(65 citation statements)
references
References 0 publications
0
60
0
5
Order By: Relevance
“…Treatment and prognosis depend on several factors, including stage, tumour grade, depth of myometrial penetration, cervical penetration and nodal metastasis (Manfredi et al 2004;Kinkel et al 1999;Hricak et al 1991;Sironi et al 1992a).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment and prognosis depend on several factors, including stage, tumour grade, depth of myometrial penetration, cervical penetration and nodal metastasis (Manfredi et al 2004;Kinkel et al 1999;Hricak et al 1991;Sironi et al 1992a).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Case et al, concordance between frozen and final pathology was noted only in 67% patients for depth of myometrial invasion and 58% patients for tumor grade (Case et al 2006). The sensitivity of MRI has similarly been found to be only 54%-75% in this regard (Hricak et al 1991;Nakao et al 2006). The use of imaging (CT, MRI, and PET-CT) has been evaluated for the pre-operative assessment of lymph node metastasis in endometrial cancer.…”
Section: Surgical Staging and Related Issuesmentioning
confidence: 99%
“…The authors noted that CT had limited usefulness in determining the extent of myometrial invasion because of the absence of a lateral view) or the presence of small disease in the retroperitoneal lymph nodes [5]. Interestingly, no mention was made of use of transvaginal sonography in the preoperative workup but MRI was rejected as a cost-effective method for preoperative evaluation patients with endometrial cancer because of its limited accuracy in evaluating para-aortic lymph nodes [6]. Lastly, elevated serum CA-125 levels were also mentioned, with the authors noting that elevated preoperative levels have been demonstrated to correlate with both advanced disease and positive lymph nodes [7].…”
Section: Evolving Gynecologic Oncology Textbookmentioning
confidence: 99%